Insights into non-thermal plasma chemistry of acetone diluted in N2/O2 mixtures: a real-time MS experiment. Issue 34 (23rd August 2022) - Thomas, Sébastien; Blin-Simiand, Nicole; Héninger, Michel; Jeanney, Pascal; Lemaire, Joel; Magne, Lionel; Mestdagh, Hélène; Pasquiers, Stéphane; Louarn, Essyllt
Abstract : Chemical Ionization Mass spectrometry is used to unveil in real-time sub-products formation during acetone degradation in a N2 /O2 homogeneous plasma reactor. Abstract : Understanding non-thermal plasma reactivity is a complicated task as many reactions take place due to a large energy spectrum. In this work, we used a well-defined photo-triggered non-filamentous discharge to study acetone decomposition in N2 /O2 gas mixtures. The plasma reactor is associated to a compact chemical ionization FTICR mass spectrometer (BTrap) in order to identify and quantify in real-time acetone and by-products in the plasma. Presence of oxygen (1 to 5%) decreased notably acetone degradation. A tremendous change is observed in the by-products distribution concomitantly to a global decrease of their total concentration. While main products observed in oxygen-free gas mix are nitrile compounds, in oxygenated media they are replaced by formaldehyde, methanol and ketene. Methanol is maximum for 1% of O2 whereas formaldehyde and ketene concentration reach their maximum value at the highest oxygen concentration tested (5%). A number of nitrate, nitrite and isocyanate organic compounds (C1 and C2) are observed as well with HNO2, HNO3 and HNCO.